STRUCTURAL METAPHOR IN THE NOVEL A MAN CALLED OVE BY FREDRIK BACKMAN - Ida Ayu Tilem Sedana Yogi; Ida Ayu Made Puspani; Putu Lirishati Soethama (Universitas Warmadewa, 2026)
This article entitled Structural Metaphor in The Novel A Man Called Ove by Fredrik Backman, aims to identify and analyze structural metaphors and their underlying meanings. The data were collected from dialogues and narrative passages, specifically phrases, clauses, and sentences within the novel. Employing a documentation method and note-taking technique, the study was conducted using a descriptive qualitative approach. The analysis was presented in informal through descriptive discussion in paragraph form. The theories applied in this study were the theory of metaphor proposed by Lakoff and Johnson (2003) to analyze the type of metaphor, especially structural metaphor. This study focused on finding structural metaphors out of three types of metaphors, and also focused on analyzing the meaning of the metaphor. The result of the study shows that there are representations of structural metaphor in the novel, and all the meanings implied by each of the metaphors are found, highlighting their central role in expressing grief and emotional transformation. These metaphors illuminate the protagonist's internal struggles and reveal universal aspects of the human experience, such as loss, grief, resilience, and the search for connection.